FACTORS AFFECTING ONLINE SHOPPING BEHAVIOR FOR NET-GENERATION IN JABODETABEK - Hendrapawoko, Kunto; Setiawaty, Lily; Situmorang, Marsaulina Elisabet; Ernawan, Rahmadi; Odata, Ratna Dharmayanti (ASEAN Marketing Journal, 2021)
Manuscript type: Research paper Research Aims: This research was conducted to examine the factors which influence the online shopping behaviour of the Net-generation in Jabodetabek. There are 10 independent variables being hypothesized to predict purchase intentions and the Net-generation behaviour in Jabodetabek as its context Design/methodology/approach: Data were collected through an online survey that targeted the Net-generation as consumers in the Jabodetabek area. A linear regression equation was used as a method to analyze this data. Research Findings: The results show that there are 5 determinant factors that promote online purchase intentions for the Net-Generation in Jabodetabek, they are social motives, enjoyment, purchase involvement, feedback and personalization. Another 5 factors were found to be less influential towards the online purchase intention, they are information abundance, product variety, responsiveness, ease of return and exchange, and the acceptance of complaints. Theoretical Contribution/Originality: By understanding the purchasing behaviour of online shopping consumers in Jabodetabek that has the largest urban population in Indonesia, one can contribute by taking a strategic role in the national growth, especially in the economic, politic and socio-cultural sectors Practitioner/Policy Implication: The results of this research can be used to help practitioners develop a marketing strategy for online shopping targeting the Net-generation in Jabodetabek as their consumers Research limitation/Implications: range age, technological exposure, spending categories, geographic difference